Evidence for an emerging disc wind and collimated outflow during an X-ray flare in the narrow-line Seyfert 1 galaxy Mrk 335. Issue 3 (25th January 2019) - Gallo, L C; Gonzalez, A G; Waddell, S G H; Ehler, H J S; Wilkins, D R; Longinotti, A L; Grupe, D; Komossa, S; Kriss, G A; Pinto, C; Tripathi, S; Fabian, A C; et al.
ABSTRACT: A triggered $140{\rm \, ks}$ XMM–Newton observation of the narrow-line Seyfert 1 (NLS1) Mrk 335 in 2015 December caught the active galaxy at its lowest X-ray flux since 2007. The NLS1 is relatively quiescent for the first ${\sim }120{\rm \, ks}$ of the observation before it flares in brightness by a factor of about five in the last $20{\rm \, ks}$ . Although only part of the flare is captured before the observation is terminated, the data reveal significant differences between the flare and quiescent phases. During the low-flux state, Mrk 335 demonstrates a reflection-dominated spectrum that results from a compact corona around a Kerr black hole. In addition to the rapid brightening, the flare is further described by spectral softening and a falling reflection fraction that are consistent with previous observations advocating at least part of the corona in Mrk 335 could be the base of an aborted jet. The spectrum during the flaring interval reveals several residuals between the 2σ and 3σ level that could be attributed to absorption lines from a highly ionized plasma that is moving outwards at $v$ ∼ 0.12 c . It could be that the increased luminosity during the flare enhances the radiation pressure sufficiently to launch a possible wind. If the wind is indeed responding to the change in corona luminosity then it must be located within ${\sim }80{\, r_{\rm g}}$ . The escape velocity at this distance is comparable to the estimated wind velocity. If confirmed, this is the first example of a radio-quiet active galactic nucleus exhibiting behaviour consistent with both diffuse and collimated outflow.